Study on the role and mechanism of lncRNA in the remodeling of atrial energy metabolism in rabbits with atrial fibrillation based on nano sensor technology. Issue 1 (1st January 2022) - Jiang, Weifeng; Xu, Ming; Qin, Mu; Zhang, Daoliang; Wu, Shaohui; Liu, Xu; Zhang, Yu
ABSTRACT: The purpose is to reveal the role and mechanism of long non-coding ribonucleic acid (lncRNA) in atrial fibrillation (AF) and atrial energy metabolism remodeling. The healthy adult New Zealand rabbit was chosen as the experimental animal, and the AF rabbit models were built. Besides, the lncRNA sequencing method based on nano sensor technology was employed to detect the differentially expressed lncRNAs, and the target lncRNA and its target genes were determined through bioinformatics analysis. Subsequently, TCONS_00016478 dysfunction experiment was performed. The gene level and protein level of TCONS_00016478, peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1-α), and its downstream genes were detected. The results show that after sequencing, 99, 755 new lncRNAs transcripts are found in total, of which 1, 215 are significantly differentially expressed, 974 are down-regulated, and 241 are up-regulated. A new transcript TCONS_00016478 associated with the remodeling of atrial energy metabolism is further screened. Silencing TCONS_00016478 can significantly reduce PGC1-α, PPARγ, GLUT4, and CPT1 expression levels (P < 0.05). Thereby, TCONS_00016478 can affect the atrial energy metabolism remodeling and atrial fibrillation in experimental rabbits by regulating the PGC1-α/PPARγ signaling pathway.